Hubungan Persepsi Pola Asuh Authoritative dan Konsep Diri dengan Perilaku Asertif pada Siswa SMK - Alfariza, Fidhiya Shabihah Alimah; Andjarsari, Fara Dwi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Assertive behavior is an ability to convey and express feelings directly and honestly without offending the feelings and rights of others. This research aims to determine the relationship between perceptions of authoritative parenting styles and self-concept with assertive behavior in vocational school students. This type of research is research with quantitative methods. The population was 216 students and the sample was 144 students. The sampling method uses proportional random sampling technique. The data collection method uses three scales, namely the assertive behavior scale, the authoritative parenting scale, and the self-concept scale using the Likert scale. Based on the results of the research analysis, it shows that there is a relationship in a positive direction between perceptions of authoritative parenting and assertive behavior of 0.333 and there is a relationship in a positive direction between self-concept and assertive behavior of 0.227. The results of data analysis with multiple correlation using SPSS 29.0 for macOS obtained a correlation coefficient of R value of 0.343 and R square of 0.118 and P = 0.001 <0.05. So it can be concluded that there is a relationship in a positive direction between perceptions of authoritative parenting and self-concept with assertive behavior in vocational students.